PENGARUH pH TERHADAP COD, BOD DAN VFA PADA PENGOLAHAN LIMBAH CAIR PABRIK KELAPA SAWIT DALAM BIOREAKTOR ANAEROBIK - Abdul Kahar (PROSIDING SEMINAR KIMIA, 2020)
ABSTRACT POME is non-toxic, but the high content of organic substances causes the value of Chemical Oxygen Demand (COD), Biological Oxygen Demand (BOD) which is still high, so that it will disturb the ecosystem if discharged directly into the environment. The pH factor plays an important role in anaerobic decomposition because in an inappropriate pH range, microbes cannot grow to the maximum and can even cause death. This research was conducted by varying the pH values namely ambient pH, pH 7.2 and pH 8 to determine the optimum pH value in the processing of POME in anerobic bioreactors. The purpose of this study was to determine the effect of pH on changes in levels of COD, BOD, and VFA in POME by using anerobic bioreactors. As for the highest % removal resulr from each of these parameters is COD atpH 7.2 is 81.51%, for BOD at ambient pH is 80.56%, and for VFA the highest is at pH 7.2 on day-21 is 8616.6. Keywords : CPO, POME, pH, anaerobic bioreactor, biogas.